A COMPUTER-BASED PROGRAM FOR PILE DESIGN WITH CONSIDERATION OF RESISTANCE, SETTLEMENT, AND NEGATIVE FRICTION SIMULTANEOUSLY (GEOMATE Journal, 2024)
Pile design is an important aspect of construction engineering, and it involves the use of physico-mechanical formulas that are suggested by national standards. Finite element software can be used to validate the results obtained from these formulas. According to design standards, pile group design usually determines the resistance capacity with a large safety factor. This safety factor is meant to maintain the elastic behavior of piles in the soil environment. However, pile group settlement is often calculated based on different theories, such as equivalent rafts, which can make it challenging for engineers to understand piles' resistance and settlement behavior. To overcome this limitation, a study was conducted using a modified Unified Method integrated with MATLAB programming. This resulted in a program that can compute the bearing capacity and validate the elastic behavior of pile-soil interaction while using reasonable safety factors. The program simultaneously calculates piles' bearing capacity and elastic settlement based on unified soil input parameters. The program was verified through the design and construction analysis of the apartment project Connect 1 in Binh Duong, Vietnam. The settlement of piles, the lengths of which were reduced from 29.0 m to 16.5 m, ranges from 2.0 to 4.5 mm, indicating that the pile-soil behavior remains elastic. This demonstrates that the program has the potential to be used in practice, at least allowing engineers to understand the unified behavior of the pile groups.